Sensory Circle Time (Sencleti): Media Pembelajaran untuk stimulasi Kemampuan Motorik Halus Anak Usia Dini: Indonesia - Fauziah, Ikrima Pebi; Harianja, Sri Indriani; Utami, Winda Sherly (Jurnal Ilmiah POTENSIA, 2025)
This study aims to examine the effect of Sencleti (Sensory Circle Time) media on fine motor skills development in children aged 4-5 years at TK Izzatul Islam Muaro Jambi. A pre-experimental design with one-group pretest-posttest was employed, involving 13 children selected through non-probability sampling techniques. Data were collected using a fine motor skills assessment rubric and analyzed using the Wilcoxon Matched Pairs Test. The results revealed a t-calculated value of 16.503, which exceeded the t-table value, indicating a significant difference between pretest and posttest scores. The findings demonstrate that Sencleti media has a significantly positive impact on fine motor skills development in children aged 4-5 years. The novelty of this research lies in the utilization of Sencleti media as an innovative learning approach that systematically combines sensory stimulation with fine motor skill development to enhance hand-eye coordination, concentration, and manipulative skills in early childhood. Future research should replicate this study with larger sample sizes and include control groups to strengthen the validity of the findings.